Upaya Pemulihan Aset Pelaku Tindak Pidana Korupsi Guna Mengoptimalisasi Kerugian Keuangan Negara - Karinda, Frans Jomar; Kristiawanto, Kristiawanto; Ismed, Mohamad (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
Functionalization of criminal law in the context of law enforcement of criminal acts of corruption, both in terms of material criminal law, formal criminal law (criminal procedural law), as well as criminal implementation, still faces obstacles, especially regarding the asset recovery policy of perpetrators of corruption which has implications for execution of payment of replacement money in order to optimize the return of state financial losses. Through the evaluation stage, it is known at this time that the criminal law has not functioned properly in tackling corruption, such as in the case of executing the payment of replacement money, where the prosecutor as the executor often has difficulty in executing the convict's property to be confiscated and auctioned to cover all or the difference in state financial losses that must be paid by the convict. This is due to the fact that the current national law still has many weaknesses that create difficulties for law enforcers in recovering the assets of perpetrators of corruption, especially in terms of confiscation of assets of perpetrators of corruption, so that the return of state financial losses caused by criminal acts of corruption when this is not optimal.Keywords: Asset Recovery; State Financial Losses AbstrakFungsionalisasi hukum pidana dalam rangka penegakan hukum tindak pidana korupsi, baik ditinjau dari sudut hukum pidana materiil, hukum pidana formil (hukum acara pidana), maupun pelaksanaan pidana, masih menghadapi kendala-kendala, terutama berkenaan kebijakan pemulihan aset pelaku tindak pidana korupsi yang berimplikasi pada pelaksanaan eksekusi pembayaran uang pengganti guna optimalisasi pengembalian kerugian keuangan negara. Melalui tahap evaluasi, diketahui saat ini bahwa hukum pidana belum berfungsi dengan baik dalam menanggulangi tindak pidana korupsi, seperti dalam hal mengeksekusi pembayaran uang pengganti, di mana Jaksa sebagai eksekutor sering kali mengalami kesulitan dalam mengeksekusi harta benda terpidana untuk disita dan dilelang guna menutupi seluruh atau selisih kerugian keuangan negara yang harus dibayarkan oleh terpidana. Hal ini disebabkan, bahwa hukum nasional saat ini masih banyak kelemahan-kelemahan yang menimbulkan kesulitan bagi penegak hukum dalam melakukan pemulihan aset pelaku tindak pidana korupsi, terutama dalam hal perampasan aset pelaku tindak pidana korupsi, sehingga pengembalian kerugian keuangan negara yang diakibatkan tindak pidana korupsi saat ini tidak optimal.Kata Kunci: Pemulihan Aset, Kerugian Keuangan Negara